Self-Assembling Nanovaccine Confers Complete Protection Against Zika Virus Without Causing Antibody-Dependent Enhancement - Rong, Heng; Qi, Mi; Pan, Jingdi; Sun, Yuhan; Gao, Jiawang; Zhang, Xiaowei; Li, Wei; Zhang, Bo; Zhang, Xian-En; Cui, Zongqiang (Frontiers in Immunology, 2022)
The Zika virus (ZIKV) epidemic poses a substantial threat to the public, and the development of safe and effective vaccines is a demanding challenge. In this study, we constructed a kind of self-assembling nanovaccine which confers complete protection against ZIKV infection. The ZIKV envelop protein domain III (zEDIII) was presented on recombinant human heavy chain ferritin (rHF) to form the zEDIII-rHF nanoparticle. Immunization of mice with zEDIII-rHF nanoparticle in the absence of an adjuvant induced robust humoral and cellular immune responses. zEDIII-rHF vaccination conferred complete protection against lethal infection with ZIKV and eliminated pathological symptoms in the brain. Importantly, the zEDIII-rHF nanovaccine induced immune response did not cross-react with dengue virus-2, overcoming the antibody-dependent enhancement (ADE) problem that is a safety concern for ZIKV vaccine development. Our constructed zEDIII-rHF nanovaccine, with superior protective performance and avoidance of ADE, provides an effective and safe vaccine candidate against ZIKV.